Stone and dung, oil and spit : Jewish daily life in the time of Jesus - Magness, Jodi. (Grand Rapids, Mich. : William B. Eerdmans Pub., 2011)
"In Stone and Dung, Oil and Spit Jodi Magness unearths 'footprints' buried in both archaeological and literary evidence to shed new light on Jewish daily life in Palestine from the mid-first century b.c.e. to 70 c.e. the time and place of Jesus' life and ministry. Magness analyzes recent archaeological discoveries from such sites as Qumran and Masada together with a host of period texts, including the New Testament, the works of Josephus, and rabbinic teachings. Layering all these sources together, she reconstructs in detail a fascinating variety of everyday activities dining customs, Sabbath observance, fasting, toilet habits, burial customs, and more"--Back cover.
Footprints in archaeology and text -- Purifying the body and hands -- Creeping and swarming creatures, locusts, fish, dogs, chickens, and pigs -- Household vessels : pottery, oil lamps, glass, stone, and dung -- Dining customs and communal meals -- Sabbath observance and fasting -- Coins -- Clothing and tzitzit -- Oil and spit -- Toilets and toilet habits -- Tombs and burial customs -- Epilogue: The aftermath of 70.
Includes bibliographical references (pages 271-305) and indexes.
Keywords: Jews -- Social life and customs -- To 70 A.D.; Jews -- History -- 586 B.C.-70 A.D.; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.